HUBUNGAN KEKURANGAN ENERGI KRONIS PADA IBU HAMIL DENGAN KEJADIAN STUNTING PADA BAYI BARU LAHIR DI WILAYAH KERJA PUSKESMAS RAMBIPUJI KABUPATEN JEMBER - Setyorini, Rahayu Gaduh Dwi; Sary, Yessy Nur Indah; Hidayati, Tutik (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
Maternal health and nutritional conditions before and during pregnancy and after delivery such as anemia and chronic energy deficiency (KEK) affect fetal growth and the risk of short birth length. Chronic Energy Deficiency (KEK) is a nutritional problem that often occurs in pregnant women. This study aims to determine the relationship between chronic energy deficiency in pregnancy and the incidence of stunting in newborns This study was a correlation design with a cross sectional approach. The population in this study were all pregnant women with SEZ in the working area of ​​the Rambi Puji Health Center, Jember Regency, involving as many as 84 participants. The sampling technique used is accidental sampling. Data were collected using a data collection sheet. Data were analyzed using Predictive Analytics SoftWare Version 18 with a chi square test at a significance level of <0.05.The results showed that most of the pregnant women did not experience chronic energy deficiency (84.5%) and most of the newborns did not experience stunting or had normal body length (84.5%). Based on the results of the analysis, it is known that there is a relationship between chronic energy deficiency in pregnant women and the incidence of stunting in newborns (p-value = 0.001 (α<0.05) and X2 = 0.403). Pregnant women with chronic energy deficiency are at risk of giving birth to stunting babies 14 times (OR=14,167).